2012
DOI: 10.1002/14651858.cd003853.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants for patients with tinnitus

Abstract: There is as yet insufficient evidence to say that antidepressant drug therapy improves tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 83 publications
(51 reference statements)
0
39
0
1
Order By: Relevance
“…Treatment with antidepressants improved comorbid depressive or anxiety disorders [144], but did not reduce tinnitus [145]. A meta-analysis of anticonvulsant treatment with carbamazepine, gabapentin and lamotrigine did not reveal additional benefits compared to placebo in controlled studies [146].…”
Section: Treatment Of Tinnitusmentioning
confidence: 99%
“…Treatment with antidepressants improved comorbid depressive or anxiety disorders [144], but did not reduce tinnitus [145]. A meta-analysis of anticonvulsant treatment with carbamazepine, gabapentin and lamotrigine did not reveal additional benefits compared to placebo in controlled studies [146].…”
Section: Treatment Of Tinnitusmentioning
confidence: 99%
“…Delayed hearing loss progression has been shown in transgenic mice with ER stress inhibitor treatment (Hu et al, 2016). Evidence of serotonin receptor mediated pathway involvement has been proposed from an apparent beneficial outcome of antidepressant usage among tinnitus patients (Baldo et al, 2012). Other pathways reaching significance include RAS, vascular smooth muscle contraction, coenzyme A biosynthesis, and NDK dynamin pathways (Gilles et al, 2017).…”
Section: Complex Genetics Approachesmentioning
confidence: 99%
“…People suffering from tinnitus go through tough time as a result of associated psychosocial [emotional and behavioural] problems which include severe headache, negative thoughts, dizziness, hearing problem, anxiety, irritation, annoyance, concentration problem, sleep difficulties, depression and poor attention focus [7]. Studies have shown that the quality of life is reduced in patients suffering from the aforementioned problems [16,19]. Meanwhile, it is noteworthy that psychoacoustical characterisation of tinnitus cannot fully determine the level of discomfort evoked by this condition.…”
Section: Tinnitus: Meaning and Effects On The Elderly Population 21 mentioning
confidence: 99%